Microstructure Characterization Techniques for Shale Reservoirs: A Review - Qian, Yujing; Gao, Ping; Fang, Xianglong; Sun, Fengrui; Cai, Yidong; Zhou, Yingfang (Frontiers in Earth Science, 2022)
The micro-structure of shale reservoirs refers to the distribution of mineral-organic matter, pore-fracture features, diagenetic processes and their interrelations. The comprehensive and accurate analysis of the shale micro-structure play a critical role in formulating reasonable development plan and optimizing measures to enhance oil or gas recovery. To explore the micro-structure characterization, the mineral and organic matter compositions, as well as the pore types and distributions of organic-rich shale reservoirs were investigated by a series of advanced techniques, including FIB-SEM and AFM. This review establishes a model of pore distribution of the layered structure of shale reservoirs based on texture simplified model. Among them, quartz laminae and carbonate laminae can be classified into grain laminae Clay minerals, organic matter and pyrite can be combined into organic matter aggregate due to the symbiotic relationship. Micro-cracks and mold holes are classified together due to diagenetic origins. At the same time, this review also systematically summarizes the micro-characterization techniques and different characteristics of organic-rich shale reservoirs, paving the way for the establishment of shale cross-scale characterization techniques.